Biochemical Properties and Potential Application of Proteases from Alkalophilic Bacillus lehensis G1 - Sulaiman, NA; Mahadi, NM; Nur Zazarina Ramly (Univ Sains Malaysia, 2024)
The biochemical properties of extracellular proteases enzymes from Malaysia Alkalophilic's bacteria, Bacillus lehensis G1, were investigated. The secreted enzymes were tested on 2% of skim milk agar. Results demonstrated that the enzyme could maintain the activity up to 60 degrees C within an extensive range of pH from 3 to 11 with the optimal pH and temperature of 7.0 and 40 degrees C, respectively. The proteases activity were also observed to be increased in the presence of several ions such as Mn2+, Fe2+, Cu2+, Mg2+ and Co2+. Whilst, the enzyme activity was marginally inhibited with the addition of Ca2+, K+ and Ni2+ with the residual activity of 85%, 81%, and 75%, respectively. Furthermore, the extracellular proteases have shown to be compatible with several Malaysia commercial liquid detergents, which could be beneficial for stain removal. The potential application of proteases in gelatine decomposition from used X-ray films was also determined in this article.